2021
DOI: 10.2478/amns.2021.1.00099
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Prediction of College Students’ Mental Health Based on K-means Clustering Algorithm

Abstract: Mental health is an important basic condition for the adult development of college students, and education workers gradually pay attention to the strengthening of mental health education for college students. In this paper, a psychological management system based on the K-means clustering analysis method is proposed. Based on the basic functions of the traditional system, the students’ psychological data are reutilised by using the idea of data mining. By optimising the iterative process of the K-means algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Yet, it performs poorly in longterm operation and maintenance, and continuing user retention is quite concerning. In 2018, ByteDance lost $1.2 billion due to TikTok's international expansion [10].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it performs poorly in longterm operation and maintenance, and continuing user retention is quite concerning. In 2018, ByteDance lost $1.2 billion due to TikTok's international expansion [10].…”
Section: Discussionmentioning
confidence: 99%
“…K-means clustering was used to characterize participants, identify the degree of heterogeneity within the population, and to identify how many clusters there were in each timepoint. The k-means clustering algorithm, specifically, was selected as it has been previously used by studies examining the mental health of university students ( Di Benedetto et al, 2019 ; Bavolar and Bacikova-Sleskova, 2020 ; Liu, 2021 ; Nelsen et al, 2021 ). The optimal number of the k-means clusters was determined using a Silhouette score and distance metric chosen was Euclidean distance.…”
Section: Methodsmentioning
confidence: 99%
“…The results demonstrated that the machine learning system predicted the treatment effect with an average accuracy of approximately 80%. Other researchers have used clinical and demographic data from patients with borderline personality disorder, in conjunction with multimodal magnetic resonance imaging and random forest models, to accurately predict treatment effects for borderline personality disorder with a sensitivity of over 70% ( Pritchard & Wilson, 2003 ; Liu, 2021 ; Means, Lichstein & Epperson, 2000 ).…”
Section: Introductionmentioning
confidence: 99%